2014
DOI: 10.1002/aic.14709
|View full text |Cite
|
Sign up to set email alerts
|

A unified theoretical model for breakup of bubbles and droplets in turbulent flows

Abstract: Pressure has a significant effect on bubble breakup, and bubbles and droplets have very different breakup behaviors. This work aimed to propose a unified breakup model for both bubbles and droplets including the effect of pressure. A mechanism analysis was made on the internal flow through the bubble/droplet neck in the breakup process, and a mathematical model was obtained based on the Young–Laplace and Bernoulli equations. The internal flow behavior strongly depended on the pressure or gas density, and based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
51
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(54 citation statements)
references
References 66 publications
3
51
0
Order By: Relevance
“…Many breakup models such as those of the works use the classical framework given in Equation , ie, they employ a total breakup rate Ω t ( v ′ ) and a separate continuous function for the daughter size distribution β ( v , v ′ ). Other breakup models, introduce kernels with an incorporated binary daughter size distribution, thereby providing the partial breakup rate Ω p ( v , v ′ ) directly. It is mirror symmetrical about v = v ′ /2 and defined by the product of the total breakup rate and the daughter size distribution Ωpfalse(v,vfalse)=Ωtfalse(vfalse)βfalse(v,vfalse). The Luo breakup model is one of the most widely used partial breakup kernels.…”
Section: Previous Workmentioning
confidence: 99%
“…Many breakup models such as those of the works use the classical framework given in Equation , ie, they employ a total breakup rate Ω t ( v ′ ) and a separate continuous function for the daughter size distribution β ( v , v ′ ). Other breakup models, introduce kernels with an incorporated binary daughter size distribution, thereby providing the partial breakup rate Ω p ( v , v ′ ) directly. It is mirror symmetrical about v = v ′ /2 and defined by the product of the total breakup rate and the daughter size distribution Ωpfalse(v,vfalse)=Ωtfalse(vfalse)βfalse(v,vfalse). The Luo breakup model is one of the most widely used partial breakup kernels.…”
Section: Previous Workmentioning
confidence: 99%
“…For example, Xing et al 10 put forward a unified mathematical model describing the bubble active breakup in turbulent flows, which predicted well both the effect of pressure/gas density on the bubble breakup rate and the different daughter size distribution. For example, Xing et al 10 put forward a unified mathematical model describing the bubble active breakup in turbulent flows, which predicted well both the effect of pressure/gas density on the bubble breakup rate and the different daughter size distribution.…”
Section: Introductionmentioning
confidence: 99%
“…Bubble breakup in a turbulent flow is determined by the hydrodynamic conditions in the surrounding liquid and the characteristic of itself, and four categories of breakup mechanisms have been summarized: turbulence fluctuation, viscous shear stress, shearing‐off process, and interfacial instability . Study on bubble breakup mainly includes macroscopic dispersion analysis and single fluid particle analysis …”
Section: Introductionmentioning
confidence: 99%
“…Garstecki et al found that bubble breakup at the T‐junction microchannel consists of two forms: squeezing regime and dripping regime . Besides, the internal flow through the bubble neck in the breakup process was measured and analyzed, and a mathematical model was proposed based on the Young–Laplace and Bernoulli equations …”
Section: Introductionmentioning
confidence: 99%